2018
DOI: 10.1002/phar.2148
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Advances in Connectivity and Community Pharmacist Patient Care Services: Implications for Patient Safety

Abstract: The scope of community pharmacy practice has expanded beyond the provision of drug product to include the provision of patient care services. Likewise, the community pharmacist's approach to patient safety must also expand beyond prevention of errors during medication dispensing to include optimization of medications and prevention of adverse events throughout the entire medication use process. Connectivity to patient data and other health care providers has been a long-standing challenge in community pharmacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Given that one of the primary roles of pharmacists is to facilitate the safe delivery of medication and minimise medication misadventure [ 21 ], the use of MHR may offer benefits that are closely aligned with pharmacists’ core professional activities. Greater access to an integrated patient record has the potential to improve safety outcomes, particularly during care transitions and for patients with increased risk of medication-related problems, such as older people [ 22 ]. Previous evidence has demonstrated that use of EHRs in the hospital setting can reduce medication-related problems [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that one of the primary roles of pharmacists is to facilitate the safe delivery of medication and minimise medication misadventure [ 21 ], the use of MHR may offer benefits that are closely aligned with pharmacists’ core professional activities. Greater access to an integrated patient record has the potential to improve safety outcomes, particularly during care transitions and for patients with increased risk of medication-related problems, such as older people [ 22 ]. Previous evidence has demonstrated that use of EHRs in the hospital setting can reduce medication-related problems [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rather than relying on patient recall alone, the use of patient-entered Health Summaries and pharmacist-entered information in a pharmacist shared medicines list on MHR may also contribute to a reduction in drug interactions between prescription and non-prescription medication. Greater access to relevant patient information creates opportunities for pharmacists to contribute to optimised treatment [ 22 ]. Digital information transfer such as through an EHR improves the speed and accuracy of information, and was considered the preferred mode of receiving information in a 2018 study of pharmacists [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, community pharmacy is quickly evolving from its roots in retail practice into crucial roles within interdisciplinary treatment teams, leaders for wellness management, and acute/chronic care providers. [92][93][94] It is thus key that as pharmacists continue to be recognized in much broader roles in the US-industry leaders and largescale employers also recognize the critical addition of addiction health care services in community pharmacy. Such a transformation in industry can only be led by sustainable payment models to support pharmacists engaging in addiction care.…”
Section: Industrymentioning
confidence: 99%
“…The Centers for Medicare and Medicaid Services recently updated the requirement of participation for long‐term care facilities, and the changes include an emphasis on the safe and effective use of medications, which is an opportunity to advance pharmacy services . Bacci and colleagues discuss the novel changes occurring in community practice as pharmacists expand their services to include patient direct care in addition to providing drug products . Overall, innovations in medication safety require a deeper understanding of ongoing and newly presenting ADRs, early warning signals for the prevention of ADRs, and an enhancement of technologies and services in all patient care settings.…”
mentioning
confidence: 99%
“…24 Bacci and colleagues discuss the novel changes occurring in community practice as pharmacists expand their services to include patient direct care in addition to providing drug products. 25 Overall, innovations in medication safety require a deeper understanding of ongoing and newly presenting ADRs, early warning signals for the prevention of ADRs, and an enhancement of technologies and services in all patient care settings.…”
mentioning
confidence: 99%